2016
DOI: 10.22302/iccri.jur.pelitaperkebunan.v32i2.229
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selection Index of Cocoa (Theobroma cacao L.) Yield Traits Using Regression Methods

Abstract: The increasing chocolate consumption has not been followed by growing production of dry cocoa beans. In order to support the increase in cocoa production, planting materials with high yield are needed. The objective of this research was to determine the components of cocoa traits affecting weight of dry cocoa beans, and set a selection index for superior cocoa trees. The experiment material were four cocoa hybrid populations of which their family ancestry were unknown, and were planted on Samigaluh Plantation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Therefore, it is pertinent to use a selection index that considers the relative importance of each variable. Setyawan, Taryono, and Mitrowihardjo (2016) emphasized the need to develop selection indexes for cocoa that gather all the variables that characterize a productive genotype. Mustiga et al (2018) and Jaimez, Vera, Mora, Loor, and Bailey (2020) also concluded that the use of selection indices can be more advantageous than direct selection, especially when characteristics of different natures are considered, such as vegetative development, morpho-agronomic fruit characteristics, productivity, and disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is pertinent to use a selection index that considers the relative importance of each variable. Setyawan, Taryono, and Mitrowihardjo (2016) emphasized the need to develop selection indexes for cocoa that gather all the variables that characterize a productive genotype. Mustiga et al (2018) and Jaimez, Vera, Mora, Loor, and Bailey (2020) also concluded that the use of selection indices can be more advantageous than direct selection, especially when characteristics of different natures are considered, such as vegetative development, morpho-agronomic fruit characteristics, productivity, and disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In the breeding context, this behaviour implies that a single measurable trait cannot be used for indirect selection purposes, but the use of a selection index containing such traits can be an interesting alternative. Setyawan et al (2016) also used path analysis to propose selection indices for cacao production components. Omotayo et al (2018) used the same technique to study the cause-and-ef-fect relationships between the traits of the cocoa bean.…”
Section: Rodrigues Et Al (2023)mentioning
confidence: 99%